Assinaturas antropogênicas de elementos maiores e traços em poeira urbana na cidade do Natal-RN - Azevedo Filho, João Batista de (2011)
Although there are many studies on urban dust contamination by heavy metals in developed countries, little attention has been paid to this type of study in developing countries, including Brazil. Therefore, a series of investigations were performed to provide signatures of heavy metals in urban dust and assess the potential sources in the city of Natal - RN-Brazil. The fraction of these sediments was studied to pass through a sieve of 63 micrometers. For the study analyzed two groups of samples, one collected in September 2009 at the end of the rainy season (9 samples) and one collected in January 2010 in the dry season (21 samples). So in all, thirty sediment samples were collected from the street. Then, in Fluorescence Spectrometry X-rays were determined major elements SiO2, Na2O, K2O, Al2O3, MgO, P2O5, Fe2O3, MnO, TiO2 and CaO, and trace Rb, Cr, Ni, Cu, Zn, Sr and Pb by an ICPOES was determined Zn, V, Na, K, Ni, Mn, Mg, P, Fe, Cr, Cu, Pb, Ba, Ca and Al from leaching HCl 0.5 mol L-1 . The results of the concentrations of elements show that the greater presence of these occurs in the dry season, except for Si which is higher in the rainy season. Analyses by geoaccumulation Index (IGEO) Enrichment Factor (EF), Contamination Factor (CF), analysis correlation and Hierarchical Cluster, confirm that Zn, Cu and Pb is anthropogenic character. Zinc may be derived from various sources related to motor vehicles or the road signs and street grids. The elements Na, K, Mg and Ca may be related to droplets suspended in air containing cations and anions present in seawater (salty), common in Christmas throughout the year, brought by winds SE-NW. The elements Na, Mg, Ca and K are the most abundant in seawater and were analyzed in this study. This indicates that the source of these additional elements detected by analyzing the contamination factor may be the very sea. Moreover, Ni, Fe, Cr and Ba can be either as a source of anthropogenic geogênica. The source of Ca is different, because it comes in lime and paint (painting guides of buildings and streets) in construction materials, but may also be present in sediments in the fragments of shells or carbonate bioclasts common in the coastal area